The Short and Long-Term Efficacy of Pulmonary Vein Isolation as a Sole Treatment Strategy for Paroxysmal Atrial Fibrillation: A Systematic Review and Meta-Analysis - Kis, Zsuzsanna; Muka, Taulant; H. Franco, Oscar; M. Bramer, Wichor; J. De Vries, Lennart; Kardos, Attila; Szili-Torok, Tamas (Current Cardiology Reviews, 2017)
Background: Pulmonary vein isolation (PVI) is an accepted treatment strategy for catheter ablation (CA) of paroxysmal atrial fibrillation (PAF). In this study, we aimed to assess the short, mid- and long-term outcome of PVI as a sole treatment strategy for PAF. Methods: Six bibliographic electronic databases were searched to identify all published relevant studies until December 14, 2015. Search of the scientific literature was performed for studies describing outcomes with mean follow-up > 24 months after PAF ablation. Only articles with 1, 3 or 5-year follow up were included, from the same group of investigators. Results: Of the 2398 references reviewed for eligibility, 13 articles (enrolling a total of 1774 patients) were included in the final analysis. Pooled analysis showed that the 12- and 62 -month success rate of a single CA procedure was 78% (95% CI 0.76% to 0.855) and 59% (95% CI 0.56% to 0.64%), respectively. The results did not differ by type of CA performed. Major complications mentioned in the enrolled studies were cerebrovascular event, pericardial tamponade and PV stenosis. Conclusion: There is a progressive and significant decline in freedom from AF between 1, 3 and 5- year after successful PVI in patients with PAF. Our analysis suggests that a high short-time success rate after PVI does not necessarily result in high chronic success rate.
Keywords: efficacy of ablation